The Effect of Capitation Acceptance on the Motivation, Discipline and Performance of Health Workers at the Bekasi City Health Center - Yuliartha Ika Putri (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This Studi aims to determine the impact of capitation acceptance on motivation, discipline, and performance of health workers in Bekasi city health center. Beside that, we also want to examine the effect of motivation on performance through work discipline. Data obtained through a questionnaire distributed to health workers in Bekasi city health center. There are two analyzes, namely: Analysis of variance (ANOVA) to find out whether there are differences in motivation, discipline and performance in each capitation group. The results show that there are no differences in motivation, discipline, and performance in the four capitations, thus that capitation does not have a significant impact on motivation, discipline, and performance of health workers in Bekasi City Health Center. The next analysis using the structural equation model (SEM) shows that there is an influence of motivation on discipline, discipline on performance, and motivation on performance. The analysis uses the SPSS program for ANOVA data processing and AMOS for SEM processing